A case of salivary duct carcinoma in the maxilla - YAMADA, Shiro; SHINOHARA, Atsushi; MORI, Atsushi; KUNO, Hajime; KAZAOKA, Yoshiaki; KAWASE, Tetsuhito (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
We describe a 55-year-old man in whom salivary duct carcinoma developed in the maxilla. He was admitted for evaluation of dysesthesia in the left buccal region. Magnetic resonance imaging revealed a 2×2cm mass in the left side of the maxilla. Biopsy of the lesion was performed under local anesthesia, and histological examination showed a malignant adenocarcinoma. The tumor originated in the minor salivary glands of the maxilla. The patient underwent maxillectomy and reconstruction with a vascularized fibula flap under general anesthesia. The postoperative histopathological diagnosis was invasion of the maxillary nerve, so the base of the skull was operated on. The patient was postoperatively given irradiation (60Gy) and chemotherapy (5 FU, CDDP). Two years later, he died of intracranial recurrence. Histopathological examination revealed comedonecrosis of the tumor nests, and the lesion was diagnosed as a salivary duct carcinoma.